Pseudomonas aeruginosa behaviour in polymicrobial communities: The competitive and cooperative interactions conducting to the exacerbation of infections - Fairoz Ali Al-Wrafy, Fairoz Ali Al-Wrafy; Reem Alariqi, Reem Alariqi; Efaq Ali Noman, Efaq Ali Noman; Adel Ali Al-Gheethi, Adel Ali Al-Gheethi; Mahdi Mutahar, Mahdi Mutahar (Elsevier, 2023)
Pseudomonas aeruginosa is mostly associated with persistent infections and antibiotic resistance as a result of several factors, biofilms one of them. Microorganisms within the polymicrobial biofilm (PMB) reveal various transcriptional profiles and affect each other which might influence their pathogenicity and antibiotic tolerance and subsequent worsening of the biofilm infection. P. aeruginosa within PMB exhibits various behaviours toward other microorganisms, which may enhance or repress the virulence of these microbes. Microbial neighbours, in turn, may affect P. aeruginosa’s virulence either positively or negatively. Such interactions among microorganisms lead to emerging persistent and antibiotic-resistant infections. This review highlights the relationship between P. aeruginosa and its microbial neighbours within the PMB in an attempt to better understand the mechanisms of polymicrobial interaction and the correlation between increased exacerbations of infection and the P. aeruginosa-microbe interaction. Researching in the literature that was carried out in vitro either in cocultures or in the models to simulate the environment at the site of infection suggested that the interplay between P. aeruginosa and other microorganisms is one main reason for the worsening of the infection and which in turn requires a treatment approach different from that followed with P. aeruginosa mono-infection.